Analisis Unsur-Unsur Komunikasi - Efendi, Erwan; Dwi, Alya; Adfi, Luthfizha; Fikri, Muhammad; Nadiyah, Ridha (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Communication (absorption from Dutch: communicatie) is "a process when a person or several people, groups, organizations and communities create and use information to connect with the environment and other people". In general, communication is an activity of conveying information, be it messages, ideas and ideas, from one party to another, carried out directly or indirectly. Communication is the process of conveying messages or information from one party to another party so that the message in question can be understood. Communication can be done verbally or nonverbally. According to experts, communication can also be defined as a process that allows someone to convey stimuli or verbal symbols to change other people's behavior. Communication has communication elements, communication elements are the basic components that form the communication process. Several elements to facilitate communication are as follows: communicator, message (massage), communicant, communication media (channel), communication method/strategy, communication effect.